DAMPAK MENGIKUTI LATIHAN ROHANI PEMULA (LRP) TERHADAP SIKAP POSITIF DAN SIKAP NEGATIF PADA TUHAN SERTA KESEHATAN METAL (MENTAL WELLBEING) - SUMARWAN, ANTONIUS; Tjahjadi, Alexander Michael; Wibisono, Henricus Soni Arya (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2023)
This study examined the impact of doing The First Spiritual Exercises (FSE) on positive and negative attitudes toward God and mental health, as measured using the Attitudes toward God Scale (ATGS-9) and the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS). Adopting a quasi-experimental research design involving 90 the FSE participants as the intervention group and 119 individuals who did not participate in the FSE as the control group, this study tested the hypotheses that doing the FSE increases Positive ATG scores, reduces Negative ATG scores, and increases Mental Health scores.The data analysis of pre-test and post-test of 164 participants (82 people from the LRP and non-LRP groups respectively), who took part fully in this study, which was conducted from 11 May to 7 June 2020, confirmed the hypotheses. Furthermore, the data shows that the FSE participation can explain 13.7% of the variability of the change in the combined score of Positive ATG, ATG Negative and Metal Health.This study provides empirical evidence on the impact of doing the Spiritual Exercises through a quantitative approach using an experimental design. In addition, this research contributes to the development of studies on spiritual practices by synergizing spiritual services, particularly the Spiritual Exercises, with research activities. It also shows that the ATGS-9 and WEMWBS scales are useful for measuring the impact of spiritual activities and services.